An empirical appraisal of the HSC level English textbook: A Bangladesh perspective - Rahman, Md Munibur; Jamila, Marium; Mamun, Md. Abdullah Al (Asian Journal of Contemporary Education, 2024)
This study aimed to critically evaluate the effectiveness and suitability of the textbook English for Today designed to instill English language skills and communicative competence into Higher Secondary Certificate (HSC) level students in Bangladesh. To carry out the research, a mixed methods approach was followed. The researchers used an adapted content analysis framework, surveyed 28 teachers and 530 students with two separate structured questionnaires, and interviewed 10 teachers to analyze the English textbook in context. The findings of this study revealed that the textbook English for Today has mixed criteria, i.e. though it fulfills several criteria of a standard English textbook, it has many shortcomings that need to be addressed. The textbook has focused much on reading and in some cases on writing skills, but the focus on listening and speaking skills is poor and paltry. The units and lessons have less clearly stated objectives in line with the curriculum, and the materials and support provided to develop language skills and communicative competence are not sufficient. The findings of this study are expected to support the teachers, textbook board authorities, syllabus designers, and writers while planning to teach or design English textbooks in English as a second language (ESL) ESL or English as a foreign language (EFL) EFL contexts.